PEMBERDAYAAN MASYARAKAT MELALUI DIGITALISASI PENGOLAHAN DATA NASABAH di BANK SAMPAH KEMUNING, JATI MELATI, KOTA BEKASI - Selfiana, Selfiana; Listiorini, Dewi; Shintya, Yana; Chaisya, Ayu Puri; Maheswari, Wulan (Universitas Mataram, 2024)
Household waste in RW 12, Jati Melati, Pondok Melati, Bekasi City if not managed properly will result in piles of garbage that pile up and cause unpleasant odor pollution. This problem can be overcome by the presence of the Kemuning Waste Bank in the local environment. The impact of the waste bank, household waste can be reduced because some of the waste is deposited into the waste bank and provides economic value for the depositor. However, there is a problem faced by the Kemuning Waste Bank, namely in terms of recording customer data which is still done manually because it does not have technological devices that support digital recording. This makes it difficult for officers to recapitulate customer data reports, present information on the amount of waste obtained based on the category and type of waste, and calculate customer savings payments when due. This activity uses the method of designing a data input system, socialization, training and mentoring. The results of Community Service Activities show that officers have the competence to input, process and present data on the same day as the day of deposit and weighing customer waste.